Airport Permits Legislative and Airport Operations Counsel's Digest Draft - J.K. MacDonald:::::: (1973)
Two drafts for legislation regarding policies for airport permits and airport operations restrictions. Includes a letter to Paul E. Wolven asking for the reactions of the Oxnard City Council.